2013
DOI: 10.1007/s11947-013-1160-2
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-Loaded Lecithin/Chitosan Nanoparticles for Functional Food Applications

Abstract: This study aimed at the encapsulation of quercetin into lecithin/chitosan nanoparticles using the electrostatic self-assembly technique, followed by evaluation of their functionality (antioxidant activity) and stability at different environmental conditions. These nanoparticles were characterized in terms of: average size, morphology, zeta potential, encapsulation efficiency, loading, and spectroscopic characteristics. Quercetin has been successfully encapsulated in lecithin/ chitosan nanoparticles with an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 32 publications
9
59
0
1
Order By: Relevance
“…We considered that high concentrations of KAE occur to decrease the spacing between nanoparticles and lead to the blockage of the repulsive interaction between the nanoparticles and aggregation. The results are in agreement with the previous studies (Barbieri et al 2013, Pool et al 2012, Souza et al 2014). Based on the results, the formulation of KAE-LC NPs nanoparticles prepared 40 lg/mL KAE concentration was further evaluated.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We considered that high concentrations of KAE occur to decrease the spacing between nanoparticles and lead to the blockage of the repulsive interaction between the nanoparticles and aggregation. The results are in agreement with the previous studies (Barbieri et al 2013, Pool et al 2012, Souza et al 2014). Based on the results, the formulation of KAE-LC NPs nanoparticles prepared 40 lg/mL KAE concentration was further evaluated.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, in the nanoparticle spectrum, the presence of an absorption band at 1230 cm À1 corresponding to P¼O stretching was indicative that ionic interactions between phosphate groups of lipids (lecithin) and amino groups of polysaccharides (chitosan) occurred. From the FTIR spectrum of KAE-LC NPs observed that encapsulation of KAE in the KAE-LC NPs was formed by what appears to be that appear by hydrophobic interactions (Souza et al 2014, Zhang et al 2008). The formation of hydrogen bonding can be also evaluated by the change in chemical shifts in NMR spectra.…”
Section: Intermolecular Interactions Between Kae and Kae-lc Npsmentioning
confidence: 99%
“…Besides, the absorption band at 1612, 1562, 1523, 1450 cm −1 of quercetin can be assigned to CC aromatic double bond stretching. The spectrum for pure quercetin was consistent with the previous studies . The IR absorption peaks of quercetin were almost as clear as that of the pure quercetin in the physical mixture, which disappeared in the encapsulating formula.…”
Section: Resultssupporting
confidence: 89%
“…The mixtures of NaC and quercetin are capable of reducing higher numbers of DPPH molecules when compared with free quercetin. This phenomenon was observed when encapsulating quercetin in polymer nanoparticles [44,45]. The absorbance of DPPH shows the lowest value when quercetin is added together with C NaC = 20 mM.…”
Section: Dpph Scavenging Activity Of Quercetinmentioning
confidence: 83%